Respuesta :

Answer:

-77

Step-by-step explanation:

We are given the equation:

[tex]\frac{3}{7} w-11=\frac{4}{7}w[/tex]

We would like to solve for w.

The first step is to isolate the variable; in other words, we need to move all the terms with w in them to one side and then all the terms without w in them to the other.

Notice that (3/7)w and (4/7)w both have w, but -11 doesn't. So, let's move (3/7)w to the right side by subtracting it from both sides:

-11 = (4/7)w - (3/7)w

On the right, we can easily subtract the fractions because they share a common denominator:

(4/7)w - (3/7)w = [(4 - 3)/7]w = (1/7)w

We now have:

-11 = (1/7)w

To finally isolate the w, we need to get rid of this fraction 1/7, so we multiply by its reciprocal, which is 7:

-11 * 7 = (1/7)w * 7

-77 = w

The answer is thus -77.

~ an aesthetics lover

ACCESS MORE